2015
DOI: 10.3389/fpls.2015.01039
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Transcriptomic Analyses of Vegetable and Grain Pea (Pisum sativum L.) Seed Development

Abstract: Understanding the molecular mechanisms regulating pea seed developmental process is extremely important for pea breeding. In this study, we used high-throughput RNA-Seq and bioinformatics analyses to examine the changes in gene expression during seed development in vegetable pea and grain pea, and compare the gene expression profiles of these two pea types. RNA-Seq generated 18.7 G of raw data, which were then de novo assembled into 77,273 unigenes with a mean length of 930 bp. Our results illustrate that tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 76 publications
(105 reference statements)
3
25
0
Order By: Relevance
“…These results suggested that these genes play a role in the sweet phenotype. At the same, the identified expression of these genes, associated with sucrose metabolism in the pea pericarp, was consistent with previous studies on pea seeds [25]. We also hypothesized that the traits of the pea pericarp could also affect the sweet traits of pea seeds.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…These results suggested that these genes play a role in the sweet phenotype. At the same, the identified expression of these genes, associated with sucrose metabolism in the pea pericarp, was consistent with previous studies on pea seeds [25]. We also hypothesized that the traits of the pea pericarp could also affect the sweet traits of pea seeds.…”
Section: Discussionsupporting
confidence: 91%
“…Vegetable pea typically has a higher content of sugar than grain pea, so it is sweeter than grain pea [25]. This remarkable phenotype characteristic has led to the division of the food-oriented pea into two types (vegetable pea and grain pea).…”
Section: Discussionmentioning
confidence: 99%
“…The presence of r or rb or bsg genes results into accumulation of low level of starch and a high level of sucrose. Recently, Liu et al (2015) performed a comparative transcroptomic analysis of genes involved in sugar and starch biosynthesis in vegetables and reported differential expression of genes related soluble sugar and starch at late development stages. Validation of RNA-Seq data was done using real-time quantitative (RT-PCR) analysis for 30 randomly selected genes which seems to be useful in garden pea breeding.…”
Section: Genome Sequencing and Transcriptome Analysis For Quality Tramentioning
confidence: 99%
“…Read assembly for separate cultivars yielded 126,335 and 145,730 contigs, respectively, with 87% showing significant expression levels in both cultivars. Later on, Liu et al sequenced samples from pea seeds harvested at the stage of 10 and 25 days after pollination and assembled 77,273 unigenes [32].…”
Section: P Sativum Transcriptomicsmentioning
confidence: 99%
“…Genes associated with sugar and starch biosynthesis were signiicantly activated during seed maturation. Analysis of diferential expression of these genes revealed a negative correlation between soluble sugar and starch lux in vegetable and grain pea seeds [32]. Alves-Carvalho et al [39] developed the Pea RNA-Seq gene atlas containing expression proiles of thousands of genes in diferent pea tissues harvested at distinct developmental stages [48].…”
Section: Diferential Gene Expression (Dge)mentioning
confidence: 99%